Illicit Ecologies: Queer Animacy and Epistemological Erasure in History of Wolves - Goldberg, Esther (Meliora, 2022)
This thesis attends to the slippages between life and nonlife in Emily Fridlunds 2017 novel History of Wolves. It traces the matter that is granted life or animacy, as well as the matter that is devitalized. Through the protagonist, Linda, the novel investigates the role of both scientific knowledge production and Christian Science in placing arbitrary biological limits on life forms, making some visible and others unseeable and unsayable. The thesis fleshes out the characters’ climate denial as yet another erasure of the animate agents. Ultimately, the thesis asks: if we can expand what is worthy of life, can we, in turn, expand what agents, actors, and matters are deserving of care?